The effect of a natural disaster on handgrip strength in prepubertal Indian children exposed to a severe cyclone during the prenatal and early postnatal growth - Sławomir Kozieł (Nature Portfolio, 2021)
Abstract Natural disasters (NDs) experienced by women and their children during prenatal and infant growth may have long-lasting effects on offspring’s development. Handgrip strength (HGS) is one of the measures of muscular strength and an indicator of health status. This study compared HGS in children exposed to cyclone Aila in India during their prenatal and infant growth compared to a control group from a non-affected, adjacent area. The total sample involved 444 boys and 423 girls aged 7–9 years, categorised into 3 groups: prenatally exposed to Aila, exposed to Aila in infancy, and the control group, non-exposed to Aila. Results revealed that prenatally exposed children of both sexes had significantly lower HGS than the controls (at least, p < 0.001 in boys; p < 0.05 in girls). On the other hand, the postnatally exposed boys, but not the girls, showed lower HGS than the controls. A significant effect of a group factor (ND exposure) on HGS was observed even after controlling for confounding variables (age, height, BMI, birth weight, gestational age; at least, p < 0.05). Our findings indicate that prenatal or early postnatal experience of a ND may have association with impaired HGS in prepubertal children.